2019
DOI: 10.3390/fluids4020095
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Internal and External Heating on the Free Convective Flow of a Bingham Fluid in a Vertical Porous Channel

Abstract: We study the steady free convective flow of a Bingham fluid in a porous channel where heat is supplied by both differential heating of the sidewalls and by means of a uniform internal heat generation. The detailed temperature profile is governing by an external and an internal Darcy-Rayleigh number. The presence of the Bingham fluid is characterised by means of a body force threshold as given by the Rees-Bingham number. The resulting flow field may then exhibit between two and four yield surfaces depending on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Most of these are boundary layer flows; see Rees 11 for a discussion of these works. A series of four papers by Rees and Bassom [12][13][14][15] is devoted to different aspects of onedimensional flows and it covers similar ground to works by Yang and Yeh 16 , Kleppe and Marner 17 , Patel and Ingham 18 , Bayazitoglu et al 19 and Barletta and Magyari 20 . Rees 21 has also presented nonlinear computations for convection in a sidewall-heated cavity and found that the presence of a Bingham fluid means that there is a critical value of the Darcy-Rayleigh number above which convection arises.…”
Section: Introductionmentioning
confidence: 95%
“…Most of these are boundary layer flows; see Rees 11 for a discussion of these works. A series of four papers by Rees and Bassom [12][13][14][15] is devoted to different aspects of onedimensional flows and it covers similar ground to works by Yang and Yeh 16 , Kleppe and Marner 17 , Patel and Ingham 18 , Bayazitoglu et al 19 and Barletta and Magyari 20 . Rees 21 has also presented nonlinear computations for convection in a sidewall-heated cavity and found that the presence of a Bingham fluid means that there is a critical value of the Darcy-Rayleigh number above which convection arises.…”
Section: Introductionmentioning
confidence: 95%
“…The convective flow of Bingham fluid in a vertical channel has also been studied; for the Couette-Poiseuille flow, the natural convection is studied in [20]. In a porous channel, the influence of exterior and internal heating on the free convective flow has been explored using Pascal's piecewise-linear law for Poiseuille flow in [21] and in [22] for mixed convection of non-Newtonian fluids, the analytic solutions have been produced.…”
Section: Introductionmentioning
confidence: 99%
“…Existence of weak solutions for the system governing the motion is investigated in [3], studies nonlinear stability of Poiseuille flow in pipes and plane channels in [4], spatial decay estimates are obtained for the problem of entry flow in a pipe in [5], and Couette-Poiseuille flow in a porous channel is studied with slip conditions in [6]. Some papers deal with the convective flow of a Bingham fluid in a vertical channel: the natural convection is studied in [7] for the Couette-Poiseuille flow and in [8,9] for the Poiseuille flow, the effect of internal and external heating on the free convective flow in a porous channel is investigated using Pascal's piecewise-linear law in [10], and the mixed convection is analyzed in [11].…”
Section: Introductionmentioning
confidence: 99%
“…10 , c 11 , c 12 are given in the Appendix A. Now, we search the plug region [y 0 , y 1 ] where y 1 satisfies the equation t 12 (y) = B, i.e.,…”
mentioning
confidence: 99%